Pengaruh Software Macromedia Flash Pada Pembelajaran dengan Model Kooperatif Tipe Team Assisted Individualization Terhadap Hasil Belajar Kimia Siswa Pada Pokok Materi Termokimia - Nurfajriani Nurfajriani; Zuhairiah Nasution (Jurnal Pendidikan Kimia (JPKim), 2015)
Abstract. This study aims to determine the effect of Macromedia Flash software on cooperative learning TAI (Team Assisted Individualization) on learning outcomes of students in the subject Thermochemistry. The population in this study were all students of class XI SMA Negeri 1 Stabat IA class on academic year of 2010/2011 consisting of 4 classes. Samples were taken by random sampling which consisted of the experimental class I and experiment II. The experimental class conduct with a model of cooperative learning TAI type of media with the use of Macromedia Flash and the experimental class II applied by cooperative learning TAI without media. The instrument used was in the form of multiple-choice test of 20 items that have been valid. Then test the hypothesis using a different test (t test). Research results obtained average value pretest experiment class I is 12.5 and the average value of the experimental class II pretest was 17.36. After the different treatment given to both classes of the average values obtained posttest experimental class I was 71.25 and the average value posttest experimental class II is 61.39. The hypothesis was tested by t test with results tcount> ttable (2.8125> 1.669) which means that the hypothesis that "there is the influence of Macromedia Flash software on the model of cooperative learning TAI type on learning outcomes of students on the subject of chemical thermochemical" unacceptable. Keywords: TAI, macromedia flash, hasil belajar